The doctrinal approach of Fatah al-Kashani - ALI HASSAN, ARKAN (International Journal of Psychosocial Rehabilitation, 2020)
The cognitive walk towards understanding the book of God Almighty Jihad in the path and grace if given it outweighs what the sun rose, and the gift of tongues and the inability of souls to perform thanks. This is why our scientists did not spare the effort and study time in seeking to reach the wishes of the Koranic text and therefore find them have enacted a way for themselves and draw a curriculum that concludes their scientific care and care of the Koran research and interpretation. What seems to me that the secret behind this is their cognitive understanding of what the Koranic text needs and of those scholars who have spared no effort. FathallahKashani (Jerusalem), the author of multiple interpretations—the interpretations—thehful in committing offenders, butter of interpretations, translation of the Koran in Persian—these works in the interpretation of the Koran indicate the care of God Almighty and reconciled him to write this abundance in the interpretation. If this indicates anything, it indicates the extent of his interest in the Holy Quran and Islamic faith, and his hard work, and great perseverance in this regard. He dealt with strong and explicit and theoretical questions of the origins of religion and Shi'a doctrines and related issues as if he were two centuries earlier; therefore, his words can be counted as the argument in this area, as he quoted in his interpretation of some of the mystical words of the senior Sufis.